2004
DOI: 10.1074/jbc.m311153200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Breast and Ovarian Tumor Growth through Multiple Signaling Pathways by Using Retrovirus-mediated Small Interfering RNA against Her-2/neu Gene Expression

Abstract: The Her-2/neu oncogene is overexpressed in ϳ30% of breast and ovarian cancer cases and often indicates a poor prognosis. Therapeutic agents against Her-2/neu have been intensively sought over the past decade. Here we show that small interfering RNA (siRNA) can silence the expression of Her-2/neu in models of human breast or ovarian cancer through retrovirus-mediated transfer of an siRNA against Her-2/neu. Cells infected with retrovirus expressing anti-Her-2/neu siRNA exhibit slower proliferation, increased apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
78
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 39 publications
12
78
0
1
Order By: Relevance
“…The inhibitory effect of trastuzumab on the expression of VEGF and IL-8 was further confirmed by ELISA analysis ( Figure 2d and e). siHER2 delivered by retrovirus has been shown to specifically affect HER2 signaling (Yang et al, 2004). As expected, siHER2 diminished the level of HER2 protein (Figure 2a).…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…The inhibitory effect of trastuzumab on the expression of VEGF and IL-8 was further confirmed by ELISA analysis ( Figure 2d and e). siHER2 delivered by retrovirus has been shown to specifically affect HER2 signaling (Yang et al, 2004). As expected, siHER2 diminished the level of HER2 protein (Figure 2a).…”
Section: Resultssupporting
confidence: 75%
“…TSP-1 is upregulated by trastuzumab treatment (Izumi et al, 2002). HER2 siRNA treatment of HER2-overexpressing BT474 cells also increases TSP-1 expression (Yang et al, 2004). Affymetrix microarray analysis indicated that treatment of BT474 cells with trastuzumab elevates TSP-1 expression (Le et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Construction of the destination vector, pDEST-CL-SI-MSCVpuro, for retroviral expression of shRNA, pCL-SI-MSCVpuro-ErbB2R-shRNA, -HPV16E6-shRNA, -p53-shRNA and -E6AP-shRNA was carried out by a previously described method (Sawada et al, 2004). The shRNA targeted sequences were as follows: HPV16E6: GTATGGAACAACATTAGAA, E6AP: 5 0 -GAAATCTAGT GAATGATGA-3 0 , p53 (18) and ErbB2 (Yang et al, 2004) as described previously. These entry vectors were recombined with pDEST-CL-SI-MSCVpuro by LR reactions (Invitrogen, Carlsbad, CA, USA), according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%